Dietary supplementation with mulberry leaf flavonoids and carnosic acid complex enhances the growth performance and antioxidant capacity via regulating the p38 MAPK/Nrf2 pathway - Liu, Chunming; Huang, Hui; Chen, Yulian; Zhou, Yingjun; Meng, Tiantian; Tan, Bihui; He, Wenxiang; Fu, Xiaoqin; Xiao, Dingfu (Frontiers in Nutrition, 2024)
Introduction This study aimed to investigate the regulatory effects of mulberry leaf flavonoids and carnosic acid complex (MCC) on the growth performance, intestinal morphology, antioxidant, and p38 MAPK/Nrf2 pathway in broilers. Methods A total of 256 healthy 8-day-old female yellow-feathered broilers were randomly divided into 4 equal groups: a control group (CON) fed a basal diet, an antibiotic group (CTC) supplemented with 50 mg/kg chlortetracycline, and two experimental groups (MCC75, MCC150) fed basal diets with 75 mg/kg and 150 mg/kg of MCC, respectively. The experiment lasted for 56 days, with days 1–28 designated as the initial phase and days 29–56 as the growth phase. Results The results on the growth performance showed that diets supplemented with MCC and CTC decreased the feed-to-gain ratio (F/G), diarrhea rate, and death rate, while significantly increasing the average daily weight gain (ADG) (p < 0.05). Specifically, the MCC150 group enhanced intestinal health, indicated by reduced crypt depth and increased villus height-to-crypt depth ratio (V/C) as well as amylase activity in the jejunum. Both the MCC and CTC groups exhibited increased villus height and V/C ratio in the ileal (p < 0.05). Additionally, all treated groups showed elevated serum total antioxidant capacity (T-AOC), and significant increases in catalase (CAT) and glutathione peroxidase (GSH-Px) activities were observed in both the MCC150 and CTC groups. Molecular analysis revealed an upregulation of the jejunal mRNA expression levels of PGC-1α, Nrf2, and Keap1 in the MCC and CTC groups, as well as an upregulation of ileum mRNA expression levels of P38, PGC-1α, Nrf2, and Keap1 in the MCC150 group, suggesting activation of the p38-MAPK/Nrf2 pathway. Discussion These findings indicate that dietary supplementation with MCC, particularly at a dosage of 150 mg/kg, may serve as a viable antibiotic alternative, enhancing growth performance, intestinal health, and antioxidant capacity in broilers by regulating the p38-MAPK/Nrf2 pathway.